To be the main leaders of our people : a history of Minnesota Ojibwe politics, 1825-1898 - Kugel, Rebecca (Native American series (East Lansing, Mich.), 1998)
In the spring of 1868, people from several Ojibwe villages located along the upper Mississippi River were relocated to a new reservation at White Earth, more than 100 miles to the west. In many public declarations that accompanied their forced migration, these people appeared to embrace the move, as well as their conversion to Christianity and the new agrarian lifestyle imposed on them. Beneath this surface piety and apparent acceptance of change, however, lay deep and bitter political divisions that were to define fundamental struggles that shaped Ojibwe society for several.